Identidades culturales a través de textos audiovisuales satíricos: El caso de "La Vida de Brian" - Valhondo Crego, José Luís (Cuadernos de Documentación Multimedia, 2018)
Life of Brian parodies a mythical narrative of Western culture in order to satirize cultural stereotypes after May 1968, at the time of transition to an economic model of global deregulation of markets. Monty Python work with detachment strategies to reenchant a depleted political sphere; however, with regard to the problem of multiculturalism, his account does not offer solutions for the diversity of the publics. Neither the old nor the new Institutions are represented by offering viable political horizons. Christianity, the Establishment or the New Left are described with scepticism at best or cynically, at worst. In short, only the posture of perplexity and astonishment of Brian serves as a common value in the construction of a public sphere whose main trait is a postmodern oxymoron, the individualistic gregariousness